Mediating Religion Through Memes: A Netnographic Comparison of Islamic and Buddhist Instagram in Indonesia - Pratama, Faishal Dhia; Truna, Dody S.; Busro, Busro (Khazanah Theologia, 2025)
Purpose: This study examines how religious messages are mediated through meme-based communication on Instagram in Indonesia by comparing Islamic and Buddhist meme accounts. It aims to clarify how different religious traditions adapt their communicative styles to a highly visual, template-driven, and participatory platform environment. Methodology: Using a qualitative netnographic approach, the study analyzed 120 meme posts (60 per account) and 3,847 user comments collected from February–April 2025 from two Indonesian Instagram accounts, @memeislam.id and @sadhu.meme. Data were coded to compare thematic patterns, visual/message framing strategies, circulation routines (posting frequency/timing, captions, hashtags, templates), and observable audience participation traces in comment threads. Findings: The analysis identified four recurring theme categories. @memeislam.id emphasized Scripture Quotation and Universal Moral Values (66.7% combined), while @sadhu.meme foregrounded Religious Satire/Humor (41.7%); both devoted an equal share to Religious Social Criticism (13.3%). Visual packaging differed in how authority and humor were rendered (e.g., short, high-readability scriptural excerpts versus citation-oriented quotation cards, alongside pop-culture meme templates). Circulation practices also diverged, including hashtag density and posting routines. Audience participation traces contrasted “rapid affirmation” (devotional phrases, emoji-only replies, tagging/mentions) with more aphoristic and concept-referential comments; captured examples showed 55,500 likes/36 comments versus 472 likes/25 comments. Implications: Findings suggest that meme-based religious communication can increase accessibility and shareability while also carrying risks of doctrinal compression and interpretive ambiguity. Practical implications include pairing meme posts with context-expanding features and strengthening digital religious literacy for audiences. Originality/Value: This study contributes an Indonesia-based, cross-religious comparison of Instagram religious memes using a shared coding framework and integrating visual-rhetorical analysis with a typology of bilingual audience response traces.